Integrative research perspectives on marine conservation. (21st December 2020) - Hillebrand, Helmut; Jacob, Ute; Leslie, Heather M.
Abstract : Whereas the conservation and management of biodiversity has become a key issue in environmental sciences and policy in general, the conservation of marine biodiversity faces additional challenges such as the challenges of accessing field sites (e.g. polar, deep sea), knowledge gaps regarding biodiversity trends, high mobility of many organisms in fluid environments, and ecosystem-specific obstacles to stakeholder engagement and governance. This issue comprises contributions from a diverse international group of scientists in a benchmarking volume for a common research agenda on marine conservation. We begin by addressing information gaps on marine biodiversity trends through novel approaches and technologies, then linking such information to ecosystem functioning through a focus on traits. We then leverage the knowledge of these relationships to inform theory aiming at predicting the future composition and functioning of marine communities. Finally, we elucidate the linkages between marine ecosystems and human societies by examining economic, management and governance approaches that contribute to effective marine conservation in practice. This article is part of the theme issue 'Integrative research perspectives on marine conservation'.